Learning Styles and Reading Comprehension Achievement: A Correlation Study - Subroto, Gatot; Vialisah, Vialisah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was aimed at knowing whether there was a correlation between students’ learning styles and their reading comprehension achievement. This research applied quantitative method, i.e., a correlation study. There were 20 eleventh-grade students of MAN Bintan participated as subject of this research. The data were collected through questionnaire and test. The questionnaire was used to know the learning styles the students have, and the test was used to know their reading comprehension achievement. In analyzing the data, the authors used Pearson Product Moment formula to figure out its coefficient correlation. In this research, the authors found that R-values of visual, auditory, and kinesthetic learning styles were 0.99, while the value of R-table was 0.468. Therefore, it can be said that there was a significant correlation between students’ learning styles and their reading comprehension achievement. Hence, learning to read as much possible as also pays attention to students’ learning styles.